Amazing landmarks : [discover the hidden stories behind 10 iconic structures!] - Rajan, Rekha S. (Scholastic Press, 2022)
"This accessible nonfiction compendium explores the creation of 10 global landmarks, from the first spark of an idea to the final layer of paint. Acclaimed educator Rekha S. Rajan encourages readers to see themselves as the engineers, builders, architects, and more through interactive stories and a unique structure"--